2021
DOI: 10.3390/cancers13184547
|View full text |Cite
|
Sign up to set email alerts
|

Clinical Applications of Minimal Residual Disease Assessments by Tumor-Informed and Tumor-Uninformed Circulating Tumor DNA in Colorectal Cancer

Abstract: Emerging data suggest that circulating tumor DNA (ctDNA) can detect colorectal cancer (CRC)-specific signals across both non-metastatic and metastatic settings. With the development of multiple platforms, including tumor-informed and tumor-agnostic ctDNA assays and demonstration of their provocative analytic performance to detect minimal residual disease, there are now ongoing, phase III randomized clinical trials to evaluate their role in the management paradigm of CRC. In this review, we highlight landmark s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(9 citation statements)
references
References 160 publications
1
8
0
Order By: Relevance
“…In cases where colorectal tumors produced CEA, ctDNA levels aligned with changes in CEA, and furthermore, both were in concordance with radiographic response assessments. Our findings are consistent with the literature showing that plasma ctDNA correlates with conventional measures of tumor response to systemic therapy (by CEA and imaging) in mCRC (12). However, unlike CEA, wherein measurable levels can be found in normal individuals but a proportion of colorectal tumors can be non-secretors of CEA, ctDNA as a measure of minimal residual disease (MRD) is a binary metric whose presence indicates that a large burden of residual metastatic cancer cells remain in one's body (13).…”
Section: Discussionsupporting
confidence: 92%
See 2 more Smart Citations
“…In cases where colorectal tumors produced CEA, ctDNA levels aligned with changes in CEA, and furthermore, both were in concordance with radiographic response assessments. Our findings are consistent with the literature showing that plasma ctDNA correlates with conventional measures of tumor response to systemic therapy (by CEA and imaging) in mCRC (12). However, unlike CEA, wherein measurable levels can be found in normal individuals but a proportion of colorectal tumors can be non-secretors of CEA, ctDNA as a measure of minimal residual disease (MRD) is a binary metric whose presence indicates that a large burden of residual metastatic cancer cells remain in one's body (13).…”
Section: Discussionsupporting
confidence: 92%
“…When purposed for detection of tumor mutations through targeted next-generation sequencing (NGS), ctDNA can be used to track dynamic changes in mutations in response to systemic therapy to detect presence of resistance mutations (12). However, in our series we have used a tumor-agnostic, methylated ctDNA marker (mSEPT9) and therefore its assessment of systemic tumor burden is not influenced by tumor mutational profile or prior therapies.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Cell-free DNA plays an increasingly pivotal role in minimal residual disease monitoring for individuals with colon cancer[ 15 ]. Both tumor-informed and tumor-agnostic approaches are being investigated[ 16 ]. The clinical case described in this paper demonstrates the prospect of using cell-free DNA for response assessment, in addition to standard tumor markers such as carcinoembryonic antigen, as illustrated in Figure 1 .…”
Section: Discussionmentioning
confidence: 99%
“…A tumor-informed assay relies on initial genomic profiling of the tumor tissues to identify tumor-derived alterations that could be evaluated and monitored using ctDNA. This approach has shown high analytical sensitivity with an improved risk of recurrence prediction ( 28 ). However, recent studies have shown that tumor-agnostic assays, that are independent on prior tumor genomic knowledge of the patient, may also achieve comparable sensitivity to tumor-informed assay in identifying patients with a higher risk of recurrence ( 19 , 21 ).…”
Section: Introductionmentioning
confidence: 99%